THE EFFECT OF A SHORT TUTORIAL ON THE INCIDENCE OF PRESCRIBING ERRORS IN PEDIATRIC EMERGENCY CARE - Kozer, Eran Kozer; Scolnik, Dennis; Macpherson, Alison; Rauchwerger, David; Koren, Gideon (Journal of Population Therapeutics and Clinical Pharmacology, 2018)
BackgroundIn the paediatric emergency department (ED) trainees are more likely to commit prescribing errors. ObjectiveTo determine whether a short educational intervention reduces the incidence of prescribing errors among trainees in a pediatric ED. MethodsA prospective cohort study at the ED of a tertiary paediatric hospital. All fellows and residents arriving at the ED at the beginning of the academic year were invited to participate in a 30-minute tutorial focusing on appropriate methods for prescribing medications, followed by a written test. Eighteen days were selected randomly during July 2001. All the charts from these days were reviewed for medication errors. Two reviewers, blinded to whether or not a particular physician attended the tutorial, independently decided whether or not an error had occurred. The main outcome measure was the number of prescribing errors. ResultsTwenty-two trainees worked in the ED during July 2001. Of these, 13 trainees attended the tutorial. Eight hundred and ninety nine orders given by trainees were evaluated. We identified 66 (12.4%) errors in 533 orders given by those who attended tutorial, and 46 (12.7%) errors in 363 orders given by those who did not attend tutorial. The adjusted odds of a medication error was not significantly different between those who did not attend the tutorial and those who did (OR: 1.07 95% CI: 0.66-1.70). ConclusionsA short tutorial, followed by a written test, administered to trainees before entering their rotation in the paediatric ED, did not appear to reduce prescribing errors.